Membuat Company Profile di Balai Besar Pelatihan Vokasi dan Produktivitas Kota Bandung Jawa Barat - Al Fauzi, Muhamad Iqbal; Suhendri (Melati Institute, 2023)
Balai Latihan Kerja is one of the companies in Bandung. Until now, the Work Training Center does not have a Company Profile to be one way of conveying information to the public. Therefore the author wants to try to make a Company Profile to help the company.The method used in creating a Company Profile is one of them using the KineMaster For PC Application. Which is where this application can be used more practically in making Company Profile.The results of making Company Profile show that companies can display Company Profile to be one method of providing information to the public.